Time frequency domain analysis on shotcrete bonding state / Mazlina Razali - Razali, Mazlina (2014)
The slope reinforcement issues in tropical soil become challenges to geotechnical engineers in designing the support system in order to prevent the major failures. Some of the major failures of shotcrete such as slope reinforcement are due to stress waves which caused by the vibration from heavy vehicles, rock deformation and shrinkage and also the blasting activity. All these causes may results to shotcrete debonded, thus reflect problems such as corrosion, buckling, fractured and internal voids creation overtime. The debonded shotcrete may cause severe instability problem.